Deadwood enrichment in Fennoscandian spruce forests – New results from the EVO experiment - Shorohova, Ekaterina; Lindberg, Henrik; Kuuluvainen, Timo; Vanha-Majamaa, Ilkka (Elsevier, 2024)
In Fennoscandian forests, evidence on the effects of variable tree retention, prescribed burning and deadwood creation on deadwood quantity and quality is still scarce. We studied the effects of prescribed burning, tree retention and downed wood creation on the deadwood profile in managed boreal Norway spruce forest stands over a 16-year period. The stand scale treatments of the experiment included cuttings with a constant volume of dispersed retention trees (50 m3 ha-1, ca. 200 trees per ha), and three levels of downed deadwood creation (5, 30 and 60 m3 ha-1), in both upland and paludified biotopes of Myrtillus site type, with or without prescribed burning, with three replicates each. After 16 years since the treatments, the diverse deadwood profiles with varying distribution by decay class were formed. The volume of deadwood varied from 9 to 107 m3 ha-1 with a mean of 65 m3 ha-1. The index of deadwood diversity was positively influenced by prescribed burning and negatively influenced by deadwood creation. The volume of all deadwood and coarse woody debris (CWD), volume and number of logs, as well as dead to live volume ratio increased after prescribed burning and with the level of deadwood creation. The positive effect of deadwood creation on the total CWD volume was higher in the upland biotopes than in the paludified ones. The highest amounts of all deadwood, CWD and logs were recorded in the upland biotopes after prescribed burning without deadwood creation. Our findings highlight the impact of tree retention with prescribed burning and deadwood creation in diversifying deadwood profile and maintaining deadwood continuum for decades.
Keywords: coarse woody debris; decay; variable retention; decomposition; diversity; fire; habitat management; nature-based forest management; rehabilitation; restoration